Interleaflet organization of membrane nanodomains: What can(not) be resolved by FRET? - Chmelová, Barbora; Davidović, David; Šachl, Radek (Biophysical journal, 2023)
Plasma membranes as well as their simplified model systems show an inherent nanoscale heterogeneity. As a result of strong interleaflet interactions, these nanoheterogeneities (called here lipid nanodomains) can be found in perfect registration (i.e., nanodomains in the inner leaflet are registered with the nanodomains in the outer leaflet). Alternatively, they might be interleaflet independent, antiregistered, or located asymmetrically in one bilayer leaflet only. To distinguish these scenarios from each other appears to be an experimental challenge. In this work, we analyzed the potential of Förster resonance energy transfer to characterize interleaflet organization of nanodomains. We generated in silico time-resolved fluorescence decays for a large set of virtual as well as real donor/acceptor pairs distributed over the bilayer containing registered, independent, antiregistered, or asymmetrically distributed nanodomains. In this way, we were able to identify conditions that gave satisfactory or unsatisfactory resolution. Overall, Förster resonance energy transfer appears as a robust method that, when using donor/acceptor pairs with good characteristics, yields otherwise difficult-to-reach characteristics of membrane lipid nanodomains.
Keywords: Fluorescence Resonance Energy Transfer; biologické modely; Lipid Bilayers; Membranes; Models, Biological; lipidové dvojvrstvy; buněčná membrána; Membrane Lipids; rezonanční přenos fluorescenční energie; membránové lipidy; membrány; Cell Membrane